Chemical Characterization and Antimicrobial Activity of Rhizome Essential Oils of Very Closely Allied Zingiberaceae Species Endemic to Borneo: Alpinia Ligulata K. Schum. and Alpinia nieuwenhuizii Val. - M. M., Yusoff; Halijah, Ibrahim; Nurulhusna, Abdul Hamid (Verlag Helvetica Chimica Acta AG, Zürich, 2011)
Two poorly studied, morphologically allied Alpinia species endemic to Borneo, viz., A. ligulata and A. nieuwenhuizii, were investigated here for their rhizome essential oil. The oil compositions and antimicrobial activities were compared with those of A. galanga, a better known plant. A fair number of compounds were identified in the oils by GC-FID and GC/MS analyses, with large differences in the oil composition between the three species. The rhizome oil of A. galanga was rich in 1,8-cineole (29.8%), while those of A. ligulata and A. nieuwenhuizii were both found to be extremely rich in (E)-methyl cinnamate (36.4 and 67.8%, resp.). The three oils were screened for their antimicrobial activity against three Gram-positive and three Gram-negative bacteria and two fungal species. The efficiency of growth inhibition of Staphylococcus aureus var. aureus was found to decline in the order of A. nieuwenhuizii>A. ligulata ∼ A. galanga, while that of Escherichia coli decreased in the order of A. galanga>A. nieuwenhuzii ∼ A. ligulata. Only the A. galanga oil inhibited the other bacteria and the fungi tested.